Pancasila-Based AI Ethics: Preventing Digital Manipulation and Deepfakes in Society - Anna Sakila; Maulidiah Yasmin; Nidaurrohmah; Royhan Ammar Sulthon (Khatulistiwa SMART: Science, Methodology, Artificial intelligence, Research, and Technology, 2025)
Deepfake is an artificial intelligence technology that is developing very rapidly and has a major impact on all aspects such as the industrial sector, education, and digital communications. In the surge in the use of Deepfake, it is not free from its misuse which can harm many people without discrimination. The absence of regulations that specifically regulate the use of Deepfake and AI technology in Indonesia has caused the legal system to be unable to quickly anticipate technological advances. Education that has not yet instilled digital ethics skills has also caused Indonesia to be a country behind in the readiness of AI regulations and ethics. The many problems and negative impacts that arise, this reality shows that the development of policies and digital ethics approaches have not been able to keep up with the development of AI technology and still need a lot of improvement. Therefore, this study aims to overcome the existing shortcomings by offering an AI ethics approach based on noble values ​​in Indonesia. Pancasila as the foundation of the state includes principles such as humanity, social justice, deliberation, and responsibility, which are very appropriate to face ethical challenges in this digital era. This study uses descriptive qualitative methods and non-participatory observation. This study examines the spread of Deepfake content on digital platforms and offers a Pancasila-based ethical framework to address the challenges of AI use. The findings show that Deepfake content is mostly used for non-consensual pornography, political manipulation, and digital fraud. Low digital literacy and the absence of specific regulations exacerbate social impacts such as polarization and loss of public trust. Pancasila, with its principles of humanity, unity, deliberation, and justice, can be the ethical foundation for strengthening regulation, education, and technology in the development of responsible and inclusive AI.